A Career Planning, Career Decisions, Career Maturity, And Career Commitment, A Descriptive Study Of The Future In Adolescents - Latersia, Dara Adiba; Lesmana, Gusman; Adifiya, Alfira (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2024)
Permasalahan yang umum terjadi pada remaja ialah kekeliruan dalam mengambil keputusan karir. Dimana persiapan mereka yang kurang dalam perencanaan karir,dan tidak adanya pengetahuan mereka dalam mengenali diri mereka sendiri. kegagalan dalam mengambil keputusan karir yang tepat adalah suatu permasalahan besar bagi diri individu, dimana ini dapat mempengaruhi kehidupan masa depan mereka. Tujuan penulisan ini untuk memberika pengetahuan bagi remaja dalam mengatasi permasalahan mereka serta memberikan layanan dengan pendektaan Trait and Factor (konseling karir) sebagai alat untuk konselor dalam membantu remaja dengan permasalahan tersebut. Dimana menggunakan metode studi deskriptif dengan penggunaan kajian pustaka. Dapat diketahui informasi yang di dapatkan sudah dari sumber-sumber yang releate. Dapat di ketahui trait and factor bisa membantu siswa dalam mengurangi kecemasan dan kekhawatiran remaja dalam menghadapi masalah mengambil keputusan yang tepat untuk masa depan mereka. A common problem that occurs in teenagers is mistakes in making career decisions. Where their preparation is lacking in career planning, and their lack of knowledge in recognizing themselves. Failure to make the right career decisions is a big problem for individuals, where this can affect their future lives. The purpose of this writing is to provide knowledge for teenagers in overcoming their problems and provide services using the Trait and Factor approach (career counseling) as a tool for counselors in helping teenagers with these problems. Where using a descriptive study method with the use of literature review. It can be seen that the information obtained has come from relevant sources. It can be seen that Trait and Factor can help students reduce the anxiety and fear of teenagers in facing the problem of making the right decisions for their future.